2007
DOI: 10.1530/rep-06-0171
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of oxygen transport-limited follicle growth

Abstract: Mathematical modelling was used to investigate oxygen transport in the developing ovarian follicle. In contrast to previous findings, the results show that oxygen can reach the oocyte in large preantral follicles. This is largely due to the inclusion of fluid voidage in the model and improved estimates of oxygen diffusion coefficients through the granulosa. The results also demonstrate that preantral follicles will eventually reach a size beyond which further growth will result in the follicle becoming increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 33 publications
4
59
0
1
Order By: Relevance
“…18,19 Efficient revascularization after tissue grafting contributed to the resumption of ovarian function and the longevity of the graft. For a metabolically active tissue such as the ovary, diffusion is limited to a couple hundred microns 35 and the presence of empty follicles in the grafts is believed to be a result of ischemia as was reported by Dolmans and colleagues. 36 Therefore, the survival of developing follicles is dependent on revascularization.…”
Section: Discussionmentioning
confidence: 81%
“…18,19 Efficient revascularization after tissue grafting contributed to the resumption of ovarian function and the longevity of the graft. For a metabolically active tissue such as the ovary, diffusion is limited to a couple hundred microns 35 and the presence of empty follicles in the grafts is believed to be a result of ischemia as was reported by Dolmans and colleagues. 36 Therefore, the survival of developing follicles is dependent on revascularization.…”
Section: Discussionmentioning
confidence: 81%
“…indeed. may even be the stimulus for antral formation (Redding et al 2007(Redding et al , 2008. However, previously we have reported that HIF activity is not associated with follicular growth at any stage of mouse ovarian folliculogenesis, but is evident immediately following the ovulatory signal, associated with granulosa cell luteinisation (Tam et al 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Predicted and actual measurements of oxygen concentration in antral follicles are similar to those in venous blood (Redding et al, 2008). Thus, the oxygen supply to the oocyte may only be limited at the late preantral to early antral stage and at the early preovulatory stage (Redding et al, 2007(Redding et al, , 2008. Follicle angiogenesis at these stages could be crucial for oocyte oxygen-ation and development (Van Blerkom, 2000).…”
Section: Carbohydrate Metabolism Throughout Folliculogenesismentioning
confidence: 90%
“…When the growing follicle reaches a size at which supply from theca capillaries could be compromised, because of the thickening and nutritional requirements of the GC layer, the follicular fluid acts as a source of oxygen and nutrients (Redding et al, 2007). Mathematical modeling was used to study the mean oxygen concentration in human follicles; and predicted a low oxygen concentration within large preantral follicles, yet sufficient to reach the oocyte (Redding et al, 2007).…”
Section: Carbohydrate Metabolism Throughout Folliculogenesismentioning
confidence: 99%
See 1 more Smart Citation